Bacterial Diversity Evolution in Maya Plaster and Stone Following a Bio-Conservation Treatment - Jroundi, Fadwa; Elert, Kerstin; Ruiz-Agudo, Encarnación; Gonzalez-Muñoz, María Teresa; Rodriguez-Navarro, Carlos (Frontiers in Microbiology, 2020)
To overcome the limitations of traditional conservation treatments used for protection and consolidation of stone and lime mortars and plasters, mostly based on polymers or alkoxysilanes, a novel treatment based on the activation of indigenous carbonatogenic bacteria has been recently proposed and applied both in the laboratory and in situ. Despite very positive results, little is known regarding its effect on the evolution of the indigenous bacterial communities, specially under hot and humid tropical conditions where proliferation of microorganisms is favored, as it is the case of the Maya area. Here, we studied changes in bacterial diversity of severely degraded tuff stone and lime plaster at the archeological Maya site of Copan (Honduras) after treatment with the patented sterile M-3P nutritional solution. High-throughput sequencing by Illumina MiSeq technology shows significant changes in the bacterial population of the treated stones, enhancing the development of Arthrobacter, Micrococaceae, Nocardioides, Fictibacillus, and Streptomyces, and, in one case, Rubrobacter (carved stone blocks at Structure 18). In the lime plaster, Arthrobacter, Fictibacillus, Bacillus, Agrococcus, and Microbacterium dominated after treatment. Most of these detected genera have been shown to promote calcium carbonate biomineralization, thus implying that the novel bio-conservation treatment would be effective. Remarkably, the treatment induced the reduction or complete disappearance of deleterious acid-producing bacteria such as Marmoricola or the phylum Acidobacteria. The outcome of this study demonstrates that such a bio-conservation treatment can safely and effectively be applied on temples, sculptures and stuccos of the Maya area and, likely, in other hot and humid environments.